Effect of different preparation methods on the properties of the textile structure of the common oxide group Al2O3 / CdO (Latakia University Journal -Basic Sciences Series, 2018)
Samples were prepared in different ways of Al2O3 / CdO and with one specific mole Al / Cd: 1-0.25 mol, in the wet joint deposition method. - The thermal disintegration of aluminum nitrate Al(NO3)3.9H2O and Cd(NO3)2.4H2O nitrate, and the reaction of aluminum nitrate Al(NO3)3.9H2O and cadmium nitrate Cd(NO3)2.4H2O, with NH4HCO3 with appropriate reactivity ratios, Sodium laureth sulfate (ALS), and the effect of various methods of preparation on the properties of the textile structure of the common oxide group .It was found that the values of porous structure factors vary according to the method of preparation, the two samples prepared in the manner of thermal disintegration. The total pore size is slightly increased, while the mean pore radius decreases from 2.71nm to 2.37nm, in contrast to the two hydrothermal heating samples.The total pore size increases significantly to 0.553ml /g. (SLS), a decrease in the radius of the middle pores, and an increase in the value of the surface area.